A Dispute with Hill’s Conception of the “New Hume” - Parusniková, Zuzana (Teorie vědy / Theory of Science, 2013)
The New Hume Debate has dominated the interpretations of Hume’s philosophy in the last few decades. James Hill in his contribu- tion in this journal (2011) supports the central claim of the New Hume, defining Hume as an epistemological sceptic and an ontological realist. I raise certain objections to Hill’s views. Some concern the confusions in the definition of realism and, on a more general level, question the meaningfulness of the whole New Hume project. Some concern Hill’s arguments focused specifically on Hume’s Dialogues, in which he claims to have found further con- firmation of Hume’s realism with regard to Causation.